Chondrogenic Bone Tumors: The Importance of Imaging Characteristics - Engel, Hannes; Herget, Georg W.; Füllgraf, Hannah; Sutter, Reto; Benndorf, Matthias; Bamberg, Fabian; Jungmann, Pia M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background Chondrogenic tumors are the most frequent primary bone tumors. Malignant chondrogenic tumors represent about one quarter of malignant bone tumors. Benign chondrogenic bone tumors are frequent incidental findings at imaging. Radiological parameters may be helpful for identification, characterization, and differential diagnosis.Methods Systematic PubMed literature research. Identification and review of studies analyzing and describing imaging characteristics of chondrogenic bone tumors.Results and conclusions The 2020 World Health Organization (WHO) classification system differentiates between benign, intermediate (locally aggressive or rarely metastasizing), and malignant chondrogenic tumors. On imaging, typical findings of differentiated chondrogenic tumors are lobulated patterns with a high signal on T2-weighted magnetic resonance imaging (MRI) and ring- and arc-like calcifications on conventional radiography and computed tomography (CT). Depending on the entity, the prevalence of this chondrogenic pattern differs. While high grade tumors may be identified due to aggressive imaging patterns, the differentiation between benign and intermediate grade chondrogenic tumors is challenging, even in an interdisciplinary approach.Key Points: Citation FormatHintergrund Chondrogene Tumoren sind die häufigsten primären Knochentumoren. Maligne chondrogene Tumoren repräsentieren etwa ein Viertel der malignen Knochentumoren. Benigne chondrogene Knochentumoren sind häufige radiologische Zufallsbefunde. Radiologische Parameter können hilfreich sein zur Identifikation, Charakterisierung und Differenzialdiagnostik.Methode Systematische Literaturrecherche mittels PubMed. Identifikation und kritische Beurteilung von Studien, welche die Bildgebung chondrogener Knochentumoren analysieren oder beschreiben.Ergebnisse und Schlussfolgerung Nach der World-Health-Organization (WHO)-Klassifikation von 2020 werden benigne, intermediäre (lokal aggressiv oder selten metastasierend) und maligne chondrogene Tumoren unterschieden. Das typische radiologische Bild chondrogen differenzierter Tumoren ist gekennzeichnet durch ein lobuliertes Wachstumsmuster mit einem hohen Signal in T2-gewichteten Sequenzen in der Magnetresonanztomografie (MRT) und durch ein meist ring- und bogenförmiges Verkalkungsmuster in der Projektionsradiografie und der Computertomografie (CT). In Abhängigkeit der Entität ist dieses typische Muster unterschiedlich ausgeprägt. Während hochmaligne Tumoren häufig ein eindeutig malignes Wachstumsmuster zeigen, ist die Differenzierung zwischen benignen und intermediären chondrogenen Tumoren auch interdisziplinär schwierig.Kernaussagen: Zitierweise
Keywords: cartilage; neoplasms; chondroma; osteochondroma; chondrosarcoma; diagnostic imaging